Development Of Local History-Based Virtual Reality Media to Improve Practical History Skills - Ofianto, -; Mulyani, Fini Fajri; Ningsih, Tri Zahra; Putri, Suci Kurnia (Society of Visual Informatics, 2025)
The acquisition of historical thinking skills is crucial for students, particularly in the areas of interpreting, documenting, and communicating information from diverse historical sources. These competencies are essential in educational media that supports learning. As such, this project aims to develop a virtual reality (VR) platform that will augment students' critical thinking abilities by presenting a range of historical sources. The research and development (R&D) process followed four key steps: defining, designing, developing, and disseminating. The study involved six teams of professional validators, two history professors, and 150 class XI students who comprised the subject sample. These stakeholders evaluated the viability of the product and the effectiveness of the media being developed. Data was gathered through teacher interviews, expert validation, and descriptive exams. Descriptive analysis was employed to assess the validity and practicality of the media, while the t-test and N-Gain were used to measure its effectiveness. Expert validation yielded an average score of 4.28, indicating good quality. The average score from practical testing by teachers and students was 4.40, demonstrating that VR media can be effectively utilized in history education. Notably, students exhibited a 69% N-Gain score, signifying increased proficiency in using VR material. These findings underscore the potential of VR media as a feasible, reliable, practical, and successful tool for enhancing practical historical skills in history education.